Kajian Intertekstual Terhadap Motif Paulus dalam Mengubah 'Menerima' (Mzm. 68:19) menjadi 'Memberi' (Ef. 4:8) - Saputra, Gilbeth Pramana; Tjong, Andrew Lucas (JURNAL ILUMINASI, 2025)
Psalm 68:19 and Ephesians 4:18 are indeed related: for Paul quotes the verse as a passage in Ephesians. However, Paul's citation method is polemical because there is a clear textual difference between Psalm 68:19 and Ephesians 4:8. The research results in this article use a qualitative method, a literature study involving lexical and grammatical analysis. The result of the analysis in this article is that the conversion of the word לָקַ֣חְתָּ or ἔλαβες in Psalm 68:19 to ἔδωκεν for Paul in his letter does exist. Paul's textual alteration has two factors: First, Paul's position as the Interpreter of the Bible. Thus, when quoting Psalm 68:19, Paul is not just quoting. He made an effort to interpret the quote for the Ephesians. Secondly, Paul was a Jew. The tradition of interpreting Judaic literature does seem to involve changing grammar or words in an attempt to articulate the passage so that the reader of the letter can easily understand the meaning of Psalm 68:19. Given Paul's Jewishness, the alteration of לָקַ֣חְתָּ or ἔλαβες in the original text of Psalm 68:19 to ἔδωκεν in Ephesians 4:8 is one example of the application of interpretive tradition of Judaic literature. Further analysis is needed to understand Paul's motif for citation Psalm 68:19.